Management of Acute Pancreatitis in the Pediatric Population: A Clinical Report From the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition Pancreas Committee. Issue 1 (January 2018) - Abu-El-Haija, Maisam; Kumar, Soma; Quiros, Jose Antonio; Balakrishnan, Keshawadhana; Barth, Bradley; Bitton, Samuel; Eisses, John F.; Foglio, Elsie Jazmin; Fox, Victor; Francis, Denease; Freeman, Alvin Jay; Gonska, Tanja; et al.
ABSTRACT: Background: Although the incidence of acute pancreatitis (AP) in children is increasing, management recommendations rely on adult published guidelines. Pediatric-specific recommendations are needed. Methods: The North American Society for Pediatric Gastroenterology, Hepatology and Nutrition Pancreas committee performed a MEDLINE review using several preselected key terms relating to management considerations in adult and pediatric AP. The literature was summarized, quality of evidence reviewed, and statements of recommendations developed. The authorship met to discuss the evidence, statements, and voted on recommendations. A consensus of at least 75% was required to approve a recommendation. Results: The diagnosis of pediatric AP should follow the published INternational Study Group of Pediatric Pancreatitis: In Search for a CuRE definitions (by meeting at least 2 out of 3 criteria: (1) abdominal pain compatible with AP, (2) serum amylase and/or lipase values ≥3 times upper limits of normal, (3) imaging findings consistent with AP). Adequate fluid resuscitation with crystalloid appears key especially within the first 24 hours. Analgesia may include opioid medications when opioid-sparing measures are inadequate. Pulmonary, cardiovascular, and renal status should be closely monitored particularly within the first 48 hours. Enteral nutrition should be started as early as tolerated, whether through oral, gastric, or jejunal route. Little evidence supports the use of prophylactic antibiotics, antioxidants, probiotics, and protease inhibitors. Esophago-gastro-duodenoscopy, endoscopic retrograde cholangiopancreatography, and endoscopic ultrasonography have limited roles in diagnosis and management. Children should be carefully followed for development of early or late complications and recurrent attacks of AP. Conclusions: This clinical report represents the first English-language recommendations for the management of pediatric AP. Future aims should include prospective multicenter pediatric studies to further validate these recommendations and optimize care for children with AP.